Ketengikan Minyak Dan Lemak Karena Oksidasi - D Karyadi (Jurnal Kimia dan Kemasan, 1999)
Oil and fat can be changed to become rancid. Rancidity of oils and fats may be caused by oxidative rancidity, enzymatic rancidity and hydrolytic rancidity. The most common rancidity o..f oils and fats are caused by atmosphere air oxidation. The damaged oils and fats which highly heat are caused by oxidation and polimerization process. Oxidation of oils and fats will result : aldehide compound, ketone, hydrocarbon, alcohol, lactone and aromatc compound which have rancid odor and bitter flavour. The factors which can accelerate the oxidation are radiation (heat and light), oxidizing agent, metal catalist andorganic catalist "Which is heat labile.